Efficacy and safety of nanoparticle albumin-bound paclitaxel plus cisplatin or nedaplatin plus tegafur/gimeracil/oteracil as induction chemotherapy regimen for hypopharyngeal cancer - Jiang, Cailing; Liu, Yulan; Mo, Yunyan; Xu, Lieyin; Zhu, Lin; Li, Zhenya; Xu, Shengyuan; Qin, Xi; Wu, Guangteng; Kang, Mafei; He, Xiaosong; Xue, Feng (Frontiers in Oncology, 2025)
BackgroundTreatment of hypopharyngeal carcinoma involves surgery, radiotherapy, and chemotherapy. The combination of docetaxel, cisplatin, and 5-fluorouracil as a standard induction chemotherapy regimen allows enhanced laryngeal preservation after surgery. In this study, our objective was to retrospectively analyze the short-term efficacy and adverse events of nab-paclitaxel plus cisplatin or nedaplatin plus tegafur/gimeracil/oteracil as an induction chemotherapy regimen for hypopharyngeal cancer.MethodsThis retrospective study involved 19 patients who received nab-paclitaxel plus cisplatin/nedaplatin plus tegafur/gimeracil/oteracil every 21 days intervals for three cycles at the Affiliated Hospital of Guilin Medical University (December 2020 to February 2023). The primary endpoint was progression-free survival. Adverse events were assessed in all patients.ResultsTreatment response was evaluated after the second cycle. Clinical outcomes indicated that 2 (10.53%), 15 (78.94%), and 2 (10.53%) patients exhibited clinical complete response, partial response, and stable disease, respectively. The objective response and disease control rates were 89.47% (17/19) and 100%, respectively. The pathological complete response rate was 71.43% (5/7) among the seven patients who underwent surgery after three cycles. Following induction chemotherapy, 4 (21.05%), 2 (10.53%), and 2 (10.53%) patients received radiotherapy, chemotherapy, and chemotherapy plus immunotherapy, respectively, whereas 4 (21.05%) patients discontinued treatment. At the 17.43-month median follow-up, median progression-free survival was 17.6 months (95% confidence interval, 13.9-21.2). The most common grade 3 treatment-related adverse events were alopecia (36.8%), leukopenia (26.3%), and anemia (15.8%). No grade 4/5 treatment-emergent adverse events were observed.ConclusionsThe combination of nab-paclitaxel, cisplatin/nedaplatin, and tegafur/gimeracil/oteracil is a safe induction chemotherapy for treating hypopharyngeal cancer.